Progressive Christianity from the Perspective of Constructive-Decolonial Theology: A Mirror of Liminal Space for Contemporary Theology - Tampilang, Risno (Sekolah Tinggi Teologi Kadesi Yogyakarta, 2024)
The emergence of the progressive Christian movement has sparked controversy and is considered a deviation from traditional Christian teachings. However, on the other hand, progressive Christianity is also seen as an effort to contextualize the Christian faith within the ever-evolving realities of the times. This research uses a qualitative method with a descriptive approach to illustrate the phenomenon of progressive Christianity. The aim of this study is to explore progressive Christianity and its development from the perspective of constructive-decolonial theology, thereby opening a more constructive paradigm in line with contemporary human life. Progressive Christianity is viewed as a